2018
DOI: 10.1016/j.ijheh.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential removal of human pathogenic viruses from sewage by conventional and ozone treatments

Abstract: Sewage contains a mixed ecosystem of diverse sets of microorganisms, including human pathogenic viruses. Little is known about how conventional as well as advanced treatments of sewage, such as ozonation, reduce the environmental spread of viruses. Analyses for viruses were therefore conducted for three weeks in influent, after conventional treatment, after additional ozonation, and after passing an open dam system at a full-scale treatment plant in Knivsta, Sweden. Viruses were concentrated by adsorption to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 47 publications
3
54
1
2
Order By: Relevance
“…So far, reports with quantified HEV concentrations in environmental waters are rare and mainly restricted to wastewater influent samples. The HEV concentrations in wastewater influents determined in this study correspond to the concentrations reported by Rodriguez-Manzano et al (2010), Masclaux et al (2013), Wang et al (2018b) and Miura et al (2016). In contrast to the findings of Masclaux et al (2013), where HEV RNA was detected more frequently in summer, no clear seasonal pattern of HEV RNA occurrence was observed in the present study, similar to the report of Ram et al (2016).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…So far, reports with quantified HEV concentrations in environmental waters are rare and mainly restricted to wastewater influent samples. The HEV concentrations in wastewater influents determined in this study correspond to the concentrations reported by Rodriguez-Manzano et al (2010), Masclaux et al (2013), Wang et al (2018b) and Miura et al (2016). In contrast to the findings of Masclaux et al (2013), where HEV RNA was detected more frequently in summer, no clear seasonal pattern of HEV RNA occurrence was observed in the present study, similar to the report of Ram et al (2016).…”
Section: Discussionsupporting
confidence: 84%
“…Ultracentrifugation and PEG precipitation are standard virus concentration methods for detection of HEV in sewage samples (Clemente-Casares et al 2003;Rodriguez-Manzano et al 2010;Masclaux et al 2013;Myrmel et al 2015;Ram et al 2016;Iaconelli et al 2017;Wang et al 2018b;Matos et al 2018). The 25% positive samples during the 1-year period using the PEG precipitation method were comparable to findings of Masclaux et al (2013) and Miura et al (2016), which reported rates of 32% and 22%, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…The conventional wastewater treatment reveals difficulty in removing both chemical and biological emerging contaminants from water [1][2][3][4][5][6][7]. Among these pollutants, pharmaceutical and personal care products, as well as enteric pathogens [8][9][10][11][12], are of concern.…”
Section: Introductionmentioning
confidence: 99%
“…Newly built libraries were amplified for 8 cycles and purified with AMPureXP-beads (Beckman Coulter, Brea, CA, USA) and thereafter analysed and loaded on an ion 318 chip and sequenced on an IonTorrent PGM with an Ion-PGM-Hi-Q-View-Sequencing Kit (ThermoFisher) as previously described [33]. The sequences obtained were imported into a CLC Genomic Workbench 9.5.1 (Qiagen, Hilden, Germany) and analysed as previously described [33]. The contigs and singleton reads were blasted against known HEV genomes using BLASTn, and a cut-off for E-value of 10 -3 for significant hits.…”
mentioning
confidence: 99%